Pengaruh Kepemimpinan, Disiplin Kerja, dan Motivasi Terhadap Kepuasan Kerja Karyawan PDAM Tirta Manuntung di Kota Balikpapan - Yemisa Melsinti Kia; Syahril Hasan; Tutik Yuliani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The presence of human resources in a company is crucial, which necessitates focusing on aspects related to employees. The purpose of this study is to examine the influence of Leadership, Discipline, and Motivation on Employee Job Satisfaction at PDAM Tirta Manuntung, Balikpapan City. This study employs a quantitative approach. The sampling technique was conducted using a Likert scale and involved 79 employees of PDAM Tirta Manuntung, Balikpapan City, as respondents. Data analysis in this study was performed using the SmartPLS method. Data collection was carried out through a questionnaire designed based on the Likert scale to assess employees' perceptions of leadership, work discipline, and motivation variables. The results of the study show that the leadership variable has a significant effect on employee job satisfaction at PDAM Tirta Manuntung, Balikpapan City. The work discipline variable has no significant effect on employee job satisfaction at PDAM Balikpapan City, and the motivation variable has a significant effect on employee job satisfaction at PDAM Tirta Manuntung, Balikpapan City.